OLAPARIB IN COMBINATION WITH ABIRATERONE IN PATIENTS WITH METASTATIC CASTRATION-RESISTANT PROSTATE CANCER: A SYSTEMATIC REVIEW (CIPEEX, 2025)
Metastatic castration-resistant prostate cancer (mCRPC) is characterized by high levels of prostate-specific antigen even in scenarios with serum testosterone levels lower than those of castration. Thus, it consists of a tumor progression resistant to androgen blockade therapy. In this context, the objective of this study is to evaluate the efficacy and tolerability of Olaparib in combination with Abiraterone compared to placebo plus Abiraterone in patients with mCRPC. This work is a systematic literature review, whose data were obtained from the search for primary studies in the Embase, Medline, Lilacs, Cochrane Central Register of Controlled Trials, and PubMed databases. The search was based on the use of the following health descriptors in English: "Castration-Resistant Prostatic Neoplasms"; "Drug Therapy"; "Abiraterone Acetate" and "Olaparib". The obtained results evidenced that the use of Olaparib in monotherapy or in association with Abiraterone demonstrated significant benefits in progression-free survival and overall survival in patients with mCRPC harboring BRCA1, BRCA2, and ATM mutations whose disease had progressed with a next-generation hormonal agent. This same benefit was also observed in the general trial population with alterations in homologous recombination repair genes. Therefore, it is concluded that this combination results in a combined antitumor effect, which implies a better quality of life for the patient under treatment, optimizing pain relief and any other complications inherent to a metastatic disease requiring palliative therapy.
Keywords: Metastatic Castration-Resistant Prostate Cancer; Antineoplastic Protocols; Olaparib; Abiraterone